2016
DOI: 10.1371/journal.pone.0158205
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Treatment with Liraglutide, a Glucagon-Like Peptide-1 (GLP-1) Receptor Agonist, Has No Effect on β-Amyloid Plaque Load in Two Transgenic APP/PS1 Mouse Models of Alzheimer’s Disease

Abstract: One of the major histopathological hallmarks of Alzheimer’s disease (AD) is cerebral deposits of extracellular β-amyloid peptides. Preclinical studies have pointed to glucagon-like peptide 1 (GLP-1) receptors as a potential novel target in the treatment of AD. GLP-1 receptor agonists, including exendin-4 and liraglutide, have been shown to promote plaque-lowering and mnemonic effects of in a number of experimental models of AD. Transgenic mouse models carrying genetic mutations of amyloid protein precursor (AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 73 publications
0
22
0
Order By: Relevance
“…We sought to confirm the efficacy of anti‐PD1 treatment in a range of different amyloid‐developing transgenic models used extensively for pharmacological testing in our respective groups (Asberom et al, ; Blanchard et al, ; Deleye et al, ; Games et al, ; Hansen et al, ; Janus et al, ). These strains develop amyloid pathology at different rates and can produce amyloid deposits of significant, compact nature (high thioflavine S reactivity: ThyAPP/PS1 M146L, and ThyAPP/PS1 A246E ) or mostly diffuse deposits (PD‐APP) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…We sought to confirm the efficacy of anti‐PD1 treatment in a range of different amyloid‐developing transgenic models used extensively for pharmacological testing in our respective groups (Asberom et al, ; Blanchard et al, ; Deleye et al, ; Games et al, ; Hansen et al, ; Janus et al, ). These strains develop amyloid pathology at different rates and can produce amyloid deposits of significant, compact nature (high thioflavine S reactivity: ThyAPP/PS1 M146L, and ThyAPP/PS1 A246E ) or mostly diffuse deposits (PD‐APP) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, amyloid plaque load was reduced, inflammation was reduced in the cortex, and neurogenesis was enhanced in the dentate gyrus (McClean et al, 2015). On the contrary, other authors did not report beneficial effects of liraglutide on cerebral plaque load, in APP/PS1 transgenic mouse models of AD with two different clinical APP/PS1 mutations (Hansen et al, 2016). In the mouse model, memory deficit was improved by subcutaneous administration of liraglutide (25 nmol/day once daily for 8 week), decreasing the phosphorylation of tau (Qi et al, 2016).…”
Section: Glp-1ras As Neuroprotective Agents In Neurodegenerative Disementioning
confidence: 93%
“…Based on that hypothesis, and our previous research in STZ-icv rat model pointing to the altered homeostasis of GLP-1 in plasma in early sAD stage, and capability of oral galactose to improve it (Knezovic et al, 2018), we have hypothesized that transgenic model of fAD might have different response to oral galactose treatment. The preclinical studies of GLP-1 agonists showed mostly positive results in transgenic mice fAD models (Cai et al, 2018;Cao et al, 2018;Chen et al, 2017;Long-Smith et al, 2013;McClean et al, 2015;McClean and Holscher, 2014;McClean and Hölscher, 2014;Tai et al, 2018b) and STZ-icv rat model of sAD (S. Li et al, 2012;Shi et al, 2017;Solmaz et al, 2015), but there are also reports of a possible inefficiency of incretin-based drugs in AD models (Hansen et al, 2016) (Bomba et al, 2013). Therefore, it is necessary to characterize in depth and compare the incretin-related metabolic profile in fAD and sAD animal models.…”
Section: Theorymentioning
confidence: 99%